2014
DOI: 10.1186/1477-7819-12-293
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing sarcoma/primitive neuroectodermal tumor of the renal pelvis: a case report

Abstract: Ewing sarcoma/primitive neuroectodermal tumor (ES/PNET) is a childhood malignancy, typically occurring in the bone and rarely in any other part of the body. We herein present a case of ES/PNET of the renal pelvis. A 37-year-old male patient presented with a chief complaint of pain in the left flank and gross hematuria. The tumor had caused moderate hydronephrosis, and ureteroscopic biopsy findings were highly suspicious of sarcoma. Subsequently, radical nephroureterectomy was performed. On the basis of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In 2014, Liu et al reported the world’s first renal pelvis ES/PNET ( 12 ). To our knowledge, very few cases of the renal pelvis, ES/PNET tumor are reported in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Liu et al reported the world’s first renal pelvis ES/PNET ( 12 ). To our knowledge, very few cases of the renal pelvis, ES/PNET tumor are reported in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…Primary renal ESFT presents major diagnostic and management hurdles for providers, as these patients most often present with advanced staging with extrarenal extension and metastases. [4][5][6][7][8][9] The optimal management of ESFT continues to be debated. However, current standard of practice invokes a combination of chemotherapy, surgical resection, and/or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rarity in presentation, there are many case reports and several case series that echo the aggressive clinical features, high propensity for metastasis, and overall poor outcome. 1,[4][5][6][7][8][9][10] In this paper, we present seven pediatric and young adult patients with primary renal ESFT and one patient with primary adrenal disease.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an ESK/PNET patient underwent radical nephroureterectomy; the patient was disease-free (i.e., no recurrence or metastasis) at 18 months postoperatively [4]. Nevertheless, ESK/PNET tumors are typically aggressive and thereby involve the lymph nodes and metastasize to lung, bone, and liver [5], demanding for multi-modality treatment.…”
Section: Discussionmentioning
confidence: 99%